Pengaruh Persepsi Harga Dan Citra Merek Terhadap Keputusan Pembelian Oli Shell (Studi Kasus Konsumen Penggunak Oli Sheel Pada CV. Sinar Mustika Wijaya) - Rahmawati, Chelly; Endriastuti, Yenia (Jurnal Mirai Management, 2024)
This study aims to determine whether price perception and brand image have a partial effect on the purchase decision of Shell oil at CV. Sinar Mustika Wijaya. The type of research used by the researcher is a quantitative method. The research technique used is multiple correlation regression. The respondents used were consumers of CV. Sinar Mustika Wijaya, the sample used was 62 respondents based on the Slovin formula. The results of the study indicate that price perception and brand image as a whole have a simultaneous and significant effect on purchasing decisions. These results can be seen based on the results of the F-Test obtained F count of 30.071. So it can be concluded that there is an influence of price perception and brand image on the purchase decision of Shell oil at CV. Sinar Mustika Wijaya. The advice given by the author in this study is to maintain or be able to adjust stable prices for buyers and maintain a good brand image so that it can increase purchasing decisions at CV. Sinar Mustika Wijaya